Cortical Spreading Depolarization in Chronic Subdural Hematoma: Bridging the Gap. (23rd January 2021) - Levesque, Mathieu; Deacon, Charles; Adam, Suzie; Iorio-Morin, Christian
ABSTRACT: Cortical spreading depolarization (CSD) is recognized as a cause of transient neurological symptoms (TNS) in various clinical entities. Although scientific literature has been flourishing in the field of CSD, it remains an underrecognized pathophysiology in clinical practice. The literature evoking CSD in relation to subdural hematoma (SDH) is particularly scarce. Patients with SDH frequently suffer from TNS, most being attributed to seizures despite an atypical semiology, evolution, and therapeutic response. Recent literature has suggested that a significant proportion of those patients' TNS represent the clinical manifestations of underlying CSD. Recently, the term Non-Epileptical Stereoytpical Intermittent Symptoms (NESIS) has been proposed to describe a subgroup of patients presenting with TNS in the context of SDH. Indirect evidence and recent research suggest that the pathophysiology of NESIS could represent the clinical manifestation of CSD. This review should provide a concise yet thorough review of the current state of literature behind the pathophysiology of CSD with a particular focus on recent research and knowledge regarding the presence of CSD in the context of subdural hematoma. Although many questions remain in the evolution of knowledge in this field would likely have significant diagnostic, therapeutic, and prognostic implications.